2018
DOI: 10.1073/pnas.1803654115
|View full text |Cite
|
Sign up to set email alerts
|

Experimental measurement of the diamond nucleation landscape reveals classical and nonclassical features

Abstract: Nucleation is a core scientific concept that describes the formation of new phases and materials. While classical nucleation theory is applied across wide-ranging fields, nucleation energy landscapes have never been directly measured at the atomic level, and experiments suggest that nucleation rates often greatly exceed the predictions of classical nucleation theory. Multistep nucleation via metastable states could explain unexpectedly rapid nucleation in many contexts, yet experimental energy landscapes suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…The formation mechanism for crustal diamonds that emerges from the present study is consistent with nucleation models via metastable molecular precursors recently proposed for nano-crystal synthesis 5154 . In particular, a nucleation pathway with tetrahedral H-terminated C groups acting as templates, before forming the sp 3 -structured C phase, resonates with Gebbie et al 51 experiments of diamond gas synthesis using diamondoid molecules as protonuclei.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The formation mechanism for crustal diamonds that emerges from the present study is consistent with nucleation models via metastable molecular precursors recently proposed for nano-crystal synthesis 5154 . In particular, a nucleation pathway with tetrahedral H-terminated C groups acting as templates, before forming the sp 3 -structured C phase, resonates with Gebbie et al 51 experiments of diamond gas synthesis using diamondoid molecules as protonuclei.…”
Section: Discussionsupporting
confidence: 90%
“…The formation mechanism for crustal diamonds that emerges from the present study is consistent with nucleation models via metastable molecular precursors recently proposed for nano-crystal synthesis 5154 . In particular, a nucleation pathway with tetrahedral H-terminated C groups acting as templates, before forming the sp 3 -structured C phase, resonates with Gebbie et al 51 experiments of diamond gas synthesis using diamondoid molecules as protonuclei. Their observation that diamond nucleation occurred through metastable, hydrogen-terminated diamond-like carbon clusters (e.g., pentamantane) led to propose a different molecular nucleation mechanism where the nucleation energetic barrier is orders of magnitude lower than that generally assumed by classical models 51 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Such a reality is close at hand. Recently, Gebbie et al 10 experimentally prepared nucleus precursors for diamond crystallization from plasma-enhanced chemical vapour deposition, and observed that isomeric precursor structures can have differing nucleation rates. The challenge for future work is to rationally design precursors to, for example, enhance nucleation rates; such work has the potential for broad impact.…”
Section: (See Section 13 In Si)mentioning
confidence: 99%